2018
DOI: 10.1016/j.firesaf.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Fire behaviour of electrical cables in cone calorimeter: Influence of cables structure and layout

Abstract: The fire performances of small telecom halogen-free cables were measured using cone calorimeter by changing several test conditions (heat flux, number and spacing of cables) and cable properties (sheath thickness and insulation mass). An analytical phenomenological fitting was proposed to predict accurately main fire performances (time-to-ignition, peaks of heat release rate and time to peak of heat release rate) from a set of 42 tests. The phenomenological model also assesses quantitatively the influence of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…In fact, the heat transfer is closely related with heat release rate. Magalie et al [31] conducted cone calorimeter experiment to investigate the correlation between the number of closely arranged cables and the maximum heat release rate, and proposed a prediction formula: 1.14 (9) In addition, Magalie et al compared the predicted results calculated from Formula (9) and the experimental results, verifying the accuracy of the prediction. To achieve the correlation between the number of cables and the maximum heat release rate of each cable, Formula (10) is proposed in this work.…”
Section: Flame-spread Ratementioning
confidence: 96%
“…In fact, the heat transfer is closely related with heat release rate. Magalie et al [31] conducted cone calorimeter experiment to investigate the correlation between the number of closely arranged cables and the maximum heat release rate, and proposed a prediction formula: 1.14 (9) In addition, Magalie et al compared the predicted results calculated from Formula (9) and the experimental results, verifying the accuracy of the prediction. To achieve the correlation between the number of cables and the maximum heat release rate of each cable, Formula (10) is proposed in this work.…”
Section: Flame-spread Ratementioning
confidence: 96%
“…A fire source is essential in experimental simulation. As far as we know, there are mainly four types of fire sources, including gas burner [3][4][5][6][7][8][9][10], heat radiation fire source [11][12][13][14][15][16][17][18][19][20][21], Electric heating fire source [22], and Oil pan fire source [23,24]. Although these fire sources could ignite the power cable, they could not simulate the ignition of cable fire by arc discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the influence of the external heat flux and the spacing of cables on the cable fire characteristics was also investigated.18-20 Martinka et al18 investigated the fire risk of electrical cables by considering the influence of mutual spacing between the cables and the thermal conductivity of the material under the cables. Magalie et al 19 found that the number of cables and spacing of cables had an effect on the first peak heat release rate and the delay between time to ignition and the second peak heat release rate. Meinier et al20 studied the fire behavior of two halogen-free flame retardant cables used in nuclear power plants (NPPs) using the cone calorimeter.…”
Section: Introductionmentioning
confidence: 99%